Predictive value of combined analysis of pro‐NPY and ERG in localized prostate cancer. Issue 10 (6th September 2018) - Kristensen, Gitte; Røder, Martin Andreas; Berg, Kasper Drimer; Elversang, Johanna; Iglesias‐Gato, Diego; Moreira, José; Toft, Birgitte Grønkær; Brasso, Klaus
Abstract : This study aimed to investigate if combined analysis of pro‐Neuropeptide Y (NPY) and ERG expression in tumor tissue are associated with biochemical failure (BF), castration‐based treatment, castration‐resistant prostate cancer (CRPC), and prostate cancer (PCa)‐specific death for men undergoing radical prostatectomy (RP) for PCa. This study included 315 patients, who underwent RP from 2002 to 2005. Both pro‐NPY and ERG expression were analyzed using immunohistochemistry and were scored as low or high and negative or positive, respectively. Risk of BF, castration‐based treatment, CRPC, and PCa‐specific death were analyzed with multiple cause‐specific Cox regression analyses and stratified cumulative incidences using competing risk assessment. Median follow‐up was 13.0 years (95% CI: 12.7–13.2). In total, 85.7% were pro‐NPY high and 14.3% were pro‐NPY low. The combined analyses of pro‐NPY and ERG expression was not associated with risk of BF (p = 0.7), castration‐based treatment (p = 0.8), CRPC (p = 0.4) or PCa‐specific death (p = 0.5). In the multiple cause‐specific Cox regression analysis, pro‐NPY high and ERG positivity was not associated with BF (HR: 1.02; 95% CI 0.6–1.7; p = 0.94). In conclusion the combination of pro‐NPY and ERG expression did not show association with risk of BF, castration‐based treatment, CRPC, and PCa‐specific death following RP.